Effect of transplanting dates and crop geometry on growth, quality, yield and profitability of papaya (Carica papaya L.) cv. Red Lady-786 (Indian Journal of Arid Horticulture, 2025)
Field experiments were conducted at four adjoining farmer's field in district Sirohi of Rajasthan during 2012-13 and 2013-14. The experiments comprised of three transplanting dates i.e. first week of March (Temp. 30°C, RH 42%), first week of July (Temp. 35°C, RH 60%), first week of September (Temp. 32°C, RH 70%)] and three crop geometries followed were 3m x 3m (1111 plants ha'), 2m x 2m (2500 plants ha"), 2.5m x 1.6m (2500 plants ha"). The experiments were replicated four times in a Randomized Block Design. Results revealed that the maximum seedling survival per cent at 20 DAT (89.30%) and 30 DAT (81.45%) was recorded in T, treatment (1" September + 2.5m x 1.6m). The combination of crop geometry of 3m x 3m and transplanting date in first week of March (T,) resulted maximum plant height (289.61 cm), stem girth (50.76 cm), number of leaves (42.45), number of fruits plant' (82.46), highest average fruit weight (1.98 kg) and fruit yield plants' (163.28 kg). However, maximum fruit set (57.70 %), fruit retention (75.50 %), yield ha' (2372.47 q in two year of experimentation) and quality parameters viz., TSS (11.80°Brix), ascorbic acid (58.35 mg 100g fruit pulp), pulp thickness (3.20 cm), overall quality score of fruit (8.36) and low acidity (1.30%) with highest net return (10.689 lakh ha' in two years of experimentation) and benefit: cost ratio (4.54) was found in the combination of crop geometry of 2.5m x 1.6m and transplanting date in first week of March (T,). This led to lower virus incidence (leaf curl & ring spot virus), sun scald and frost injury symptoms.
Keywords: Papaya ring spot virus; Days After Transplanting; crop geometry; diurnal fluctuation; Dates of transplanting